Perceptions of academicians regarding assessment process of distance teacher education courses in Pakistan - Nasreen Akhter (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
This study aimed to analyze the assessment process of distance education. The study involved academicians working under distance education system as the faculty of education. It used a questionnaire depending on five point Likert scale. Its content validity and face validity was determined by expert opinion method. Reliability of tool was determined through Cronbach's alpha that was 0.83. It concluded that assignment questions were well prepared. They covered entire courses. Question papers were well balanced but validity of question papers was not determined. Furthermore, marking of assignments was not satisfactory and the institutions did not ensure accuracy of marking of assignments and answer scripts. Tutors marked assignments but did not write comments on assignments to guide students about weak portions of their responses. Results were announced late but were communicated to students just after the result declaration. This suggested that all persons involved in the assessment process should perform responsibility seriously.
Keywords: 330; ducational assessment; distance education; teacher training; assignments; examinations